Post-neurosurgical meningitis; gram negative bacilli vs. gram positive cocci - Mehdi Zeinalizadeh; Roya Yazdani; Mohammad Mehdi Feizabadi; Maryam Shadkam; Arash Seifi; Seyed Ali Dehghan Manshadi; Alireza Abdollahi; Mohammadreza Salehi (Babol University of Medical Sciences, 2022)
Background: Post-neurosurgical meningitis is a significant cause of mortality and morbidity. In this study we aimed to compare the differences of clinical, laboratory features and outcomes between the post-neurosurgical meningitis caused by gram-negative bacilli (GNB) and gram-positive cocci (GPC). Methods: Cases of post-neurosurgical meningitis (with positive CSF culture) were included. After classifying patients as GNB and GPC groups, clinical and paraclinical data were compared. Results: Out of 2667 neurosurgical patients, CSF culture was positive in 45 patients. 25 (54.3%) were GNB, 19 (41.3%) GPC. The most common microorganisms were Klebsiella pneumoniae (n=14, 31.1%), Coagulase negative staphylococcus (n=8, 17.8%), Staphylococcus aureus (n=6, 13.3%), Acinetobacter baumannii (n=4, 8.9%), Pseudomonas aeruginosa (n=2, 4.4%), and Escherichia coli (n=2, 4.4%). There were no correlation between CSF Leakage, Surgical site appearance, presence of drain, Age and GCS between two groups (P=0.11, P=0.28, P=0.06, P=0.86, P=0.11 respectively). The only different laboratory indexes were ESR (86.8 mm/h vs. 59.5 mm/h, P=0.01) and PCT (13.1 ng/ml vs. 0.8 ng/ml, P=0.02) which were higher in GNB cases. 20% (n=5) of patients with GNB meningitis received preoperative corticosteroid, while none of GPC cases received (P=0.03). The median length of hospitalization for GNB and GPC cases was 56 and 44.4 days respectively (P=0.3). Conclusion: The GNB antibiotic coverage should be designed more carefully in post-neurosurgical meningitis especially in patients with recent corticosteroid therapy and elevated ESR and procalcitonin.